Technology sharing through university industry collaboration: Innovation in Malaysian manufacturing landscape - Darshana, Kumari Raguphaty; Shamsuddin, Baharin; Faiz, Mohd Turan (Penerbit UMP, 2019)
Innovation has been the key pillar of success for economic growth especially for developing countries. Malaysia is one resorting to both universities and industries to collaborate in a more engaging and concentrated fashion to accelerate innovation growth especially in the manufacturing sector. Despite the high number of university industry collaborations, the return rate of investments is low. This suggest a mismatch between the demands of both the university and industry. On that grounds, it is important to address this research gap, for it will provide insights to help industries and universities understand how academic collaborations can be intensified to spur innovation. The aim of this paper is to establish Technology Sharing as a conduit in University Industry Collaboration to intensifying innovation within the Malaysian Manufacturing Landscape. The paper is based on findings of a quantitative approach through survey questionnaire to determine a strong relationship on Technology Sharing through University Industry Collaboration as a source of innovation in the manufacturing industry. A total of 120 companies within the manufacturing landscape were survey and analysed using paired sample T-test. The mean scores were translated into percentages to amplify the magnitude of knowledge improvement and product development with Technology Sharing in manufacturing against the Business expenditure on R&D (BERD). The findings reveal, Technology Sharing through University Industry Collaboration improves knowledge within the company significantly. This generation of new knowledge is a source of innovation in product development to enhance the product/process/technology of the manufacturing companies in Malaysia. The findings also show that with Technology Sharing, companies’ absorptive capacity of new product development is significant. Improvement of knowledge translates into product development and augments innovation. This further ascertains the relationship of Technology Sharing in intensifying University Industry Collaboration to the growth of innovation within the Malaysian Manufacturing landscape.